Performance of ionospheric maps in support of long baseline GNSS kinematic positioning at low latitudes - Park, J.; Sreeja, V.; Aquino, M.; Cesaroni, C.; Spogli, L.; Dodson, A.; De Franceschi, G. (American Geophysical Union, 2016)
Ionospheric scintillation occurs mainly at high and low latitude regions of the Earth and may impose serious degradation on GNSS (Global Navigation Satellite System) functionality. The Brazilian territory sits on one of the most affected areas of the globe, where the ionosphere behaves very unpredictably, with strong scintillation frequently occurring in the local postsunset hours. The correlation between scintillation occurrence and sharp variations in the ionospheric total electron content (TEC) in Brazil is demonstrated in Spogli et al. (2013). The compounded effect of these associated ionospheric disturbances on long baseline GNSS kinematic positioning is studied in this paper, in particular when ionospheric maps are used to aid the positioning solution. The experiments have been conducted using data from GNSS reference stations in Brazil. The use of a regional TEC map generated under the CALIBRA (Countering GNSS high-Accuracy applications Limitations due to Ionospheric disturbances in BRAzil) project, referred to as CALIBRA TEC map (CTM), was compared to the use of the Global Ionosphere Map (GIM), provided by the International GNSS Service (IGS). Results show that the use of the CTM greatly improves the kinematic positioning solution as compared with that using the GIM, especially under disturbed ionospheric conditions. Additionally, different hypotheses were tested regarding the precision of the TEC values obtained from ionospheric maps, and its effect on the long baseline kinematic solution evaluated. Finally, this study compares two interpolation methods for ionospheric maps, namely, the Inverse Distance Weight and the Natural Neighbor.